Methyldopa prescription in patients with hipertensive disease during pregnancy - Leonardo Ramos Hernández; Kenia Soyet Medina; Ronaldo Rams Aguilera; Javier Leonardo Ramos Medina; Lilian Luisa Galves Martí (Centro Provincial de Información de Ciencias Médicas, 2017)
A descriptive cross-sectional indication-prescription study of medications use, of 67 pregnant women with hipertensive disease during pregnancy, assisted in "Mariana Grajales Coello" Southern Maternal Hospital was carried out in Santiago de Cuba, from July, 2015 to June, 2016, aimed at characterizing  methyldopa prescription in these patients. The use of this medicine prevailed in the case material in patients that had situations associated with the most serious forms of the disease, such as advanced age, nonpariity and hypertension history. The main difficulties corresponded to the combination of medicines with risk of methyldopa interactions and its use at a high dose.